Fifth annual report - Mew, E. B. ; Miller, Mary F. ; Norman, E. M. ; Roberts, D. ; Galbraith, H. ; Worden, M. ; Daukes, A. ; Waterworth, E. M. ; Mottram, D. B.; Capener, Norman (1932)
1932 1932 1930s 86 pages : illustrations The twenty-four beds which are now being added to it (twelve of them for adults) will be ready, it is hoped, before the end of 1933. With the opening of an Adult Ward D.A.C.A. will take on fresh responsibilities, rendered imperatively necessary by the fact that the nearest orthopaedic hospital possessing adult accommodation is 200 miles away. The Angela Convalescent Home, Tipton St. John (so called after the lady who bequeathed the property to D.A.C.A.) is in process of equipment for the reception of 20 children between the ages of five and twelve. The scheme would scarcely have materialized without the unfailing interest and practical support of Mrs. Townsend, whose generosity has been the means of providing adequate accommodation in the Home. Many local residents have also shown valuable interest, giving contributions in kind and money, besides equally helpful personal service. Mrs. Balfour is welcomed as Chairman of the House Committee and Captain Williams, M.C., D.F.C., as the Hon. Warden in charge. H.R.H. the Duke of Connaught honoured the Angela Home by an informal visit of inspection during his stay at Sidmouth. His Royal Highness expressed approval of all he saw and spent some time talking with the Hon. Warden and some prospective patients, a few of whom were brought from the Hospital to meet him. D.A.C.A. has suffered the loss of a most valued officer in the late Mr. J. F. Wreford, who was a member of both Central Committees and Chairman of Barnstaple District Committee from the Association's beginning until the time of his death. He combined with unfailing energy a rare tact and judgment and a personality which won the confidence and affection of all who worked with him. The Association is most fortunate in securing Dr. Harper as Mr. Wreford's successor in the District Chairmanship. Mr. John Radcliffe, M.B.E., who had already given valuable service on the Employments Advisory Committee and in other ways, has become Chairman of the Exeter District Committee in succession to Lord Mamhead, who has consented to remain connected with the work as Vice-Chairman. Mr. Howard, Hon. Treasurer, has continued his devoted services and is most kindly willing to present himself again for re-election. The decision of Mr. R. S. Lang not to allow himself to be nominated again for the post of Hon. Secretary has been received with the greatest regret. He has held that position ever since the inception of the scheme, giving his services to the cause with an unfailing loyalty and enthusiasm profoundly appreciated and which will long be gratefully remembered. Miss H. Phillipps, who filled the post of Assistant Secretary with conspicuous efficiency 5 292/841.51/2/2